Effect of Temperature of Electrolyte Solution On Cu/Ni Layer On Low-Temperature Voltage Range Measurement Performance - Muhammad Ihsan; Moh. Toifur; Azmi Khusnani (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The electroplating method is considered an economical way in coating manufacture. However, this method is more widely used to treat chemical waste management and material properties engineering. The purpose of this research is to make a low-temperature sensor Cu/Ni film using an electroplating method assisted by an external magnetic field. The materials used are nickel (Ni) and copper (Cu), placed as anode and cathode. The electrolyte solution used is made from a mixture of H3BO3 (40 g/L), NiSO4 (260 g/L), and NiCl2 (60 g/L). The deposition process is carried out using an external magnetic field of 200 G and installed perpendicular to the deposition current, 120 s deposition time, and 3 Volt voltage. Preparation of Cu/Ni layer sensor samples is done by changing the electrolyte solution's temperature by varying the temperature between 30 ºC to 70 ºC with intervals of 10 ºC. The results of the research show that in testing the performance of the low-temperature sensor, each Cu/Ni layer sample has been able to offer its character as a low-temperature sensor. The character is indicated by changes in the output voltage's value following changes in the thermocouple value. Each sample at variations in the temperature of the electrolyte solution shows that the measured voltage range varies with the most extensive voltage range the sample has with deposition at 60 ºC.Keywords: Electrolyte Solution Temperature, Voltage Range, Cu/Ni layer, Low-Temperature Sensor, Electroplating.